Earthquake Fingerprint of an Incipient Subduction of a Bathymetric High - Luigi Passarelli; Simone Cesca; Nima Nooshiri; Sigurjón Jónsson (Geophysical Research Letters)
Abstract The resistance of bathymetric highs to subduction results in large‐scale morphological distortions of the outer‐rise, trench, and fore‐arc regions. Once subducted, bathymetric highs induce frictional segmentation along the plate interface that may result in increase or decrease of the plate coupling. However, the mechanics of the collision is inferred mostly from geophysical and geological surveys since earthquakes rarely illuminate finer details of the subduction of seafloor relief. A year‐long and energetic seismic sequence at the Loyalty Ridge (LR)‐Vanuatu Trench allowed us to characterize how strain is released along the collision zone. Earthquakes revealed complex fracturing in the outer‐rise and fore‐arc regions and segmentation of the interface with both limited magnitude events and aftershock productivity. The complex earthquake activity associated to the collision and subduction of the LR appears to support a frictionally segmented interface where Mw ≥ 8 megathrust earthquakes are unlikely to nucleate.